Impact of Seniors Centers on oral health-related quality of life of older adults - Luz, Fernanda W. Machado; Silva, Alexandre Emídio Ribeiro; Perroni, Ana Paula; Goettems, Marília L.; Boscato, Noéli (Revista de Saúde Pública, 2020)
OBJECTIVE: This study evaluated the oral health-related quality of life (OHRQoL) of older adults participating or not in Seniors Centers (SC). METHODS: Two independent samples were compared: older adults who participate in SC (n = 124) and older adults who visited Primary Healthcare Centers (PHC) and do not participate in SC (n = 164). The data collected consisted of sociodemographic (sex, age, educational level, marital status, family income) and psychosocial characteristics—Sense of Coherence (SOC), anxiety and depression using HADS, happiness—, and oral clinical evaluation—use and need of dental prosthesis and decayed (D), missing (M), or filled (F) teeth. The resulting OHRQoL was evaluated using the Oral Health Impact Profile (OHIP-14). The Mann-Whitney test was used to assess the associations between the independent variables and the OHIP-14. Poisson regression models were also used in the analyses (α=0.05). RESULTS: In the PHC, of the 270 individuals invited to participate in the study, 164 (60.7%) were interviewed and clinically examined; while in the SC, of the 166 individuals invited to participate in the study, 124 (74.7%) were interviewed and clinically examined. After adjustments for sociodemographic, psychosocial and clinical factors, we found that the impact on OHRQoL was 2.8 times higher (95%CI 2.0–4.2) for older adults who did not participate in SC. CONCLUSION: Older adults who participated in SC showed better perception on OHRQoL, independently of sociodemographic, psychosocial and clinical factors.